2017
DOI: 10.1515/cclm-2016-0797
|View full text |Cite
|
Sign up to set email alerts
|

Serological diagnosis and prognosis of severe acute pancreatitis by analysis of serum glycoprotein 2

Abstract: Serological diagnosis and prognosis of severe acute pancreatitis by analysis of serum glycoprotein 2 DOI 10.1515/cclm-2016-0797 Received September 6, 2016 accepted October 10, 2016; previously published online November 12, 2016 Abstract Background: Glycoprotein 2 (GP2), the pancreatic major zymogen granule membrane glycoprotein, was reported to be elevated in acute pancreatitis in animal models. Methods: Enzyme-linked immunosorbent assays (ELISAs) were developed to evaluate human glycoprotein 2 isoform al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Hao et al [ 12 ] reported that GP2 has more discriminatory power on diagnosing AP than lipase [the area under the curve (AUC): 0.96 vs 0.81]. According to another study by Roggenbuck et al [ 15 ], serum GP2 is a specific marker of AP and contributes to the prognosis of its severe form.…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al [ 12 ] reported that GP2 has more discriminatory power on diagnosing AP than lipase [the area under the curve (AUC): 0.96 vs 0.81]. According to another study by Roggenbuck et al [ 15 ], serum GP2 is a specific marker of AP and contributes to the prognosis of its severe form.…”
Section: Introductionmentioning
confidence: 99%